Best practice guidance for policymakers and stock exchanges on sustainability reporting initiatives (United Nations New YorkUS, 2014)
Aims to assist stock exchanges and regulators who have responsibility for corporate reporting practice and are contemplating the introduction of a new initiative, or further development of an existing one - to promote sustainable corporate reporting.
Keywords: FINANCIAL MARKET